Searching for competitive advantage in the black box - FLAMHOLTZ, Eric (Institutional Knowledge at Singapore Management University, 2010)
This paper deals with the sources of potential competitive advantage. It builds upon previous work by Flamholtz (1995) to develop a model of the determinants of organizational success and failure as well as subsequent empirical studies of the link between the model and financial performance (Flamholtz and Aksehirli, 2000, Flamholtz and Hua, 2002. The paper discusses the extension of the model from a framework for organizational development to a framework or ‘lens’ for building competitive advantage. It also hypothesizes that an organization’s infrastructure (defined in terms of four of the model’s variables) are likely to be the true source of sustainable competitive advantage. Data originally collected for the study reported in Flamholtz and Aksehirli to test the relation between the model and financial performance was utilized to test hypotheses concerning the model and competitive success and sources of competitive advantage. Some of the data derived from the prior study by Flamholtz and Aksehirli, which has not been previously analyzed or reported, was used to identify empirically the sources of competitive advantage, and, in turn, test the hypothesis about the role of infrastructure as the true source of sustainable competitive advantage. Two different statistical methods were used to analyze the hypothesized relationship between the variables included in the Pyramid of Organizational Development and competitive success: (1) the Friedman two-way analysis of variance by ranks and (2) regression analysis. SPSS statistical software was used for both analyses. Results of the Friedman test indicate that ROE scores are significantly associated with total Pyramid of Organizational Development scores. At the significance level of 0.005, higher values of total scores are connected with higher ROE values, and lower total scores are linked with lower ROEs [Siegel (1956)]. To address the issue of the Sources of Potential Strategic Advantage we performed an analysis of the data on strategic organizational development scores shown below in Figure 4 to determine which of the six key variables comprising the Pyramid of Organizational Development actually differentiated one firm from another. As hypothesized, we found different frequencies or proportions of the variables comprising the Pyramid of Organizational Development. We also tested the hypothesis that the key sources of competitive advantage are a firm’s infrastructure, rather than its choice of markets and its products, using the Cochran Q Test. The results of this test indicate that the proportions of competitive advantages of each matched pair do differ significantly among the different sources of potential competitive advantages, at a significance level of 0.028. In addition, to test the hypothesis that infrastructure is significantly different from markets and products, we performed a Friedman Two Way Analysis of Variance. This test was significant at 0.014. The empirical analysis above shows a clear relationship between the Pyramid of Organizational Development framework and competitive advantage. This has several significant implications for practicing managers and researchers.